HUBUNGAN ANTARA PENGGUNAAN INTERNET DENGAN PRESTASI BELAJAR - Ika Handoyo; Djalali; Igaa Noviekayati (Jurnal Psikologi Tabularasa, 2012)
Abstract The background of this research is the adolescence as internet user. If internet is used to something that have complication with study, it can be opinioned have positive relation with academic achievement, but, if internet is used to something that havent complication with study, it can be opinioned have negative relation with academic achievement. Use of internet is as an information, communication, leisure, financial transaction, and education. This study present data from rapport and survey of 140 students at GIKI 2 elementary high school. The result showed that there was not relationships between use of internet as an information, communication, leisure, financial transaction and education with academic achievement [R=0,246; R2=0,061; F=0,734; p=0,130 (p 0, 05)], this case showed that the result is not significant. It can be concluded that the use of internet cannot be increased or decrease academic achievement. Keywords: use of internet, academic achievement